Adessiivin funktion päättely paikallisessa kontekstissa - Luojola, Teemu (Virittäjä, 2007)
Determining the function of the Finnish adessive case through inference in a local context (englanti) 3/2007 (111) Determining the function of the Finnish adessive case through inference in a local context The article examines the extent to which the intended semantic meaning of Finnish nouns in the adessive case is apparent from the sentence context. Semantic and syntactic similarities are sought between sentences in which the intended meaning of the adessive is the same. The underlying theoretical assumption is that the borders between linguistic categories are fuzzy and that peoples linguistic choices are guided by functional considerations. The perspective is therefore primarily a quantitative one. The research problem, closely associated with the concept of emergence, is that the meaning of an entire sentence can not be inferred as the linear composite of its individual words. For the purposes of the study, six different functions are defined for the adessive case: as a spatial, temporal or habitive expression, and as a means of expressing what the writer refers to as instrument and means, method and quantity and state and circumstance. Nouns are divided into fourteen different categories primarily on the basis of their functional nature. The boundaries between the functions and the different categories are not seen as rigid, however. Instead, the same word can belong to different categories depending on the situation. The study data comprises all adessive-case nouns (plus their sentence contexts) appearing at least 10 times in a corpus consisting of all the 1999 editions of the Karjalainen newspaper. This amounted to a total of approximately 18,000 sentences. The results reveal that about half of the adessive-case nouns appear in just one of the adessive functions, and for only one in four of the nouns does the most common function constitute less than 90 per cent of occurrences. Each semantic category of these nouns typically has one adessive function that is plainly dominant among the occurrences for that category. The writer concludes that the most important factor in determining the function of the adessive is the semantic nature of the root. When the word context alone does not reveal the function, the second-most important factor is the sentence context. It is also evident from the study data that the sentence position has a systematic influence on the interpretation of the adessive, but this was not dealt with in any detail in this study. Teemu Luojola